2008
DOI: 10.1128/jvi.00063-07
|View full text |Cite
|
Sign up to set email alerts
|

Definition of the Minimal cis -Acting Sequences Necessary for Genome Maturation of the Herpesvirus Murine Cytomegalovirus

Abstract: Herpesvirus DNA replication proceeds via concatemeric replicative intermediates that are comprised of head-to-tail-linked genomes. Genome maturation is carried out by the terminase, a protein complex that mediates both insertion of concatemer DNA into capsids and its subsequent cleavage to release genomes within these capsids. This cleavage is sequence specific, but the governing cis-acting DNA sequences are only partially characterized. Two highly conserved motifs called pac1 and pac2 lie near the ends of her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
23
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 32 publications
3
23
0
Order By: Relevance
“…This corresponds very closely with the minimal essential region for pac1 function identified in MCMV (32). The results obtained with the pac1 substitution mutants are in good agreement with previous studies using HSV-1 amplicons and ectopic-site MCMV recombinants (10,15,32). These confirm that important sequences are present within the proximal and distal GC-rich regions but that the sequence of the T element is not crucial.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…This corresponds very closely with the minimal essential region for pac1 function identified in MCMV (32). The results obtained with the pac1 substitution mutants are in good agreement with previous studies using HSV-1 amplicons and ectopic-site MCMV recombinants (10,15,32). These confirm that important sequences are present within the proximal and distal GC-rich regions but that the sequence of the T element is not crucial.…”
Section: Discussionsupporting
confidence: 80%
“…The results reported here confirm that the pac2 region is essential for the initiation of the cleavage-packaging process and that while the sequence of the T element is critical, extensive nucleotide substitutions within the consensus, unconserved, and GC elements are tolerated. It has recently been reported that in MCMV a second essential packaging element, which is GC rich, is present within pac2 located further from the cleavage site than the T element (32). It remains possible that a corresponding signal is present in HSV-1 within the region designated "rest of Uc" and is supported by our previous observation that in the amplicon assay, deletion but not substitution of the intervening unconserved region caused a significant impairment in DNA packaging (10).…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations